2018
DOI: 10.1111/jog.13558
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of severe lacerations during forceps delivery in a single teaching hospital where simulation training is held annually

Abstract: The incidence of severe lacerations was relatively low. Risk factors for severe lacerations with forceps delivery were identified as birth weight, fetal head station, malrotation and the number of extractions. Obstetric anesthesia may protect against severe lacerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In our study, younger nulliparous women (adolescents <twenty years old and 20-29 years old) were associated with all perineal tears that were identified in previous reports. The comparative elasticity of the perineum in women who are nulliparous decreases after one or more deliveries compared to multiparous women, which result in tearing of perineum and need an episiotomy [22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, younger nulliparous women (adolescents <twenty years old and 20-29 years old) were associated with all perineal tears that were identified in previous reports. The comparative elasticity of the perineum in women who are nulliparous decreases after one or more deliveries compared to multiparous women, which result in tearing of perineum and need an episiotomy [22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that the rate of rotational abnormalities and arrest of labor increase with neuraxial labor analgesia [14,15]. Furthermore, a high fetal head station (+ 2~+ 3) and malrotation were reported to be risk factors for severe lacerations during instrumental delivery [16].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sano et al published the incidence and risk factors of severe lacerations during forceps delivery at another tertiary university hospital. 2) While these two reports focused on deliveries at tertiary hospitals, no study has yet reported on forceps delivery at obstetrics clinics in Japan. One reason is that only a few facilities in Japan perform forceps delivery, with most only performing vacuum-assisted delivery.…”
Section: Dear Editormentioning
confidence: 99%